2018
DOI: 10.1177/0198742918816447
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Research-to-Practice Gap Through Effective Professional Development for Teachers Working With Students With Emotional and Behavioral Disorders

Abstract: Students with emotional and behavioral disorders (EBD) experience a variety of externalizing and internalizing behavior problems, gaps in academic achievement, and increased rates of dropping out of school. Thus, it is essential that students with EBD receive evidence-based academic and behavioral supports from skilled and knowledgeable teachers to improve student outcomes. Unfortunately, teachers typically receive limited professional development in classroom management practices and other supports targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 53 publications
(63 reference statements)
1
37
0
2
Order By: Relevance
“…Analysis of the Wright map results suggests teachers may need additional support and training on supporting students with mental health needs such as responding to students with suicidal thoughts, discussing mental health concerns with parents/guardians, and providing academic instruction to students with internalizing and externalizing concerns. School mental health professional development should follow best practices of explicit training in evidence-based practices and intensive and ongoing professional development supports (State, Simonsen, Hirn, & Wills, 2019). Teacher preparation programs should also consider implementing preservice training opportunities and courses to proactively improve preservice teacher confidence for successfully serving expanded school mental health roles (Phillippo & Blosser, 2017; Weston et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the Wright map results suggests teachers may need additional support and training on supporting students with mental health needs such as responding to students with suicidal thoughts, discussing mental health concerns with parents/guardians, and providing academic instruction to students with internalizing and externalizing concerns. School mental health professional development should follow best practices of explicit training in evidence-based practices and intensive and ongoing professional development supports (State, Simonsen, Hirn, & Wills, 2019). Teacher preparation programs should also consider implementing preservice training opportunities and courses to proactively improve preservice teacher confidence for successfully serving expanded school mental health roles (Phillippo & Blosser, 2017; Weston et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Effective professional development systems include both initial training and ongoing coaching for implementing, sustaining, and adapting practices to better meet the needs of students and their contexts (Gettinger & Stoiber, 2016;Reddy, Dudek, & Lekwa, in press). Training is necessary to acquire the skills to implement the practices in this article, but systems for ongoing coaching, including providing educators with visual performance feedback may be needed for school personnel to implement them with fidelity (Noell, Volz, Henderson, & Williams, 2017;State, Simonsen, Hirn, & Wills, 2019).…”
Section: Professional Development Systemsmentioning
confidence: 99%
“…Previous studies have shown that teachers find it difficult to support the unique needs of students with emotional and behavioral difficulties (State, Simonsen, Hirn, & Wills, 2019; Stefan, Rebega, & Cosma, 2015; Taylor & Smith, 2019). Our findings highlight that this is also the case in bullying situations.…”
Section: Discussionmentioning
confidence: 99%